1999
DOI: 10.1021/ja982368q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 12-Substituted 1-Carba-closo-dodecaborate Anions and First Hyperpolarizability of the 12-C7H6+-CB11H11- Ylide

Abstract: Salts of 12-alkyl and 12-phenyl derivatives of the CB11H12 - anion are prepared in 50−60% yields from the 12-iodo-CB11H11 - anion by Pd-catalyzed cross-coupling with Grignard reagents. The tropylium ylide 12-C7H6 +-CB11H11 - is made in 54% yield by reaction of C7H7 + with CB11H12 -. Its ground-state dipole moment is 11.25 ± 0.1 D and its first hyperpolarizability is β = 236 × 10-30 esu at 1064 nm, as determined by hyper-Rayleigh scattering measurement. This value is ten times that of p-nitroaniline and is surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 34 publications
2
67
0
1
Order By: Relevance
“…20 Previous studies of carborane derivatives for NLO purposes have been reported. 21 The crystal The π orbital overlap between phenyl group and tangential cluster orbitals has been invoked to explain the cage C-C lengthening in aryl-ortho-carborane derivatives. 24,25 This was further explored by ab initio RHF/6-31G* and MP2/6-31G* calculational studies on 1-phenylortho-carborane and other aryl-carboranes in order to probe the orientational preferences of aryl groups attached to the carbon atoms of ortho-carborane.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…20 Previous studies of carborane derivatives for NLO purposes have been reported. 21 The crystal The π orbital overlap between phenyl group and tangential cluster orbitals has been invoked to explain the cage C-C lengthening in aryl-ortho-carborane derivatives. 24,25 This was further explored by ab initio RHF/6-31G* and MP2/6-31G* calculational studies on 1-phenylortho-carborane and other aryl-carboranes in order to probe the orientational preferences of aryl groups attached to the carbon atoms of ortho-carborane.…”
Section: Structural Aspectsmentioning
confidence: 99%
“…The strong bonds between carborane and metal combined with high electronic delocalization provide great stability and diverse applications of these compounds [3,7] in medicine [9][10][11][12] and materials sciences [13][14][15][16][17][18][19][20] [16]. In addition, Grüner et al [18] obtained a derivative [12-C 7 H + 6 -CB 11 H − 11 ] with β ten times larger than p-nitroaniline (9.2 × 10 −30 cm 5 /esu) [24]. Recently, we studied the role played by substituent effects on NLO properties of dicarba-closo-dodecarboranes isomers 1,2-(ortho-), 1,7-(meta-) and 1,12-(para-) C 2 B 10 H 12 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in this area involving carboranes include synthesis of novel compounds [14,18] and NLO properties' calculations [5,8,[15][16][17]21,28]. For example, a new class of dodecarboranes ([B 12 H 11 -C 2 B 10 H 11 ] 2− ) with potential application as NLO materials was proposed through ab initio calculations (1)…”
mentioning
confidence: 99%
“…The family of closo-carboranes (C 2 B n H n+2 , n=4-10) is characterized by high thermal stability [10], [11], [12] and these systems have been regarded as three-dimensional aromatic analogues of benzene [13]. However, very little attention has been paid to the study of carboranes as potential NLO-materials ([14], [15], [16], [17]) z and the hyperpolarizability of donor/acceptor-substituted 6-vertex carboranes has not been investigated. Earlier studies on 10-and 12-vertex boranes and carboranes [17] have suggested that these molecules may be promising candidates in the design of NLO-e®ective compounds.…”
Section: Introductionmentioning
confidence: 99%